Miracles of Jesus - Cox, Anna; Bragard, Jean-Claude ([Australia : BBC Active, 2006)
Through powerful, emotive drama, CGI, the latest scientific and historical evidence and compelling debate, this series aims to revolutionise our understanding of Jesus, bringing to life the unforgettable miracle stories the Nativity and Holy week
Ep. 1. - Galilee (58 min.) .- Ep. 2. Son of Go (58 min.) . - Ep. 3. - The most astonishing miracle of all
Executive producer (for Jerusalem Productions), Peter Elvy ; executive producer, Alan Bookbinder, Saul Nasse
Presented by Rageh Omaar
DVD format
Keywords: Jesus Christ -- Miracles; Bible. -- Criticism, interpretation, etc; Magic -- Miscellanea